SISTEM PEMBIAYAAN KESEHATAN GLOBAL - Nurrahmi Aspawati Nurrahmi Aspawati (Yayasan Pendidikan Medika Indonesia, 2021)
Health services always prioritize Universal Health Coverage (UHC) which aims to ensure that everyone, everywhere can get quality health services. Health costs can be divided into two categories, namely, money spent on personal health and money spent on public health. In 2015 worldwide, health care costs increased by more than 9 trillion spent on health care and annual spending could increase to 16 trillion by 2030. To improve the health status of a community according to the World Health Organization (WHO) a minimum budget is required. 5% - 6% of the total state budget of a country, while to achieve the ideal level of health a budget of 15% - 20% of the state budget is needed. This health expenditure has proven effective in overcoming health problems in several countries. So we need the right strategy for the management of health financing by paying attention to all aspects. Health insurance is the ideal choice for managing the global health financing system. Following the health insurance program should be done from an early age.